Psychological Influences on Investment Choices: A Deep Dive into Chinese Investor Behavior - Yuan, Huipeng; DuraiPandi, Oyyappan (Journal of Ecohumanism, 2024)
Through a systematic literature review, this paper provides insights into the psychological and behavioural factors that influence Chinese investors' investment decisions. It is found that Chinese investors' behaviours are influenced by a complex interaction of cultural values (e.g. Confucianism), economic factors and the regulatory environment. Common psychological biases such as overconfidence, loss aversion and herding behaviour are prevalent among Chinese investors but are often moderated by cultural factors. Influenced by cultural norms, Chinese investors generally exhibit a long-term investment orientation and high savings rates. The study also found that the fast-growing technology sector and the property market are notable areas of investment activity in China, demonstrating both successes and failures. In addition, regulatory changes and government policies play an important role in shaping investor sentiment and decision-making. However, existing research remains deficient, particularly with regard to the interaction between cultural factors and individual investor characteristics, as well as institutional investor behaviour. This study provides insights into the unique aspects of Chinese investment psychology and behaviour for regulators, investors and financial institutions, contributing to a better understanding and characterisation of the Chinese investment marke